Foot deformities in patients with diabetic mellitus (with and without peripheral neuropathy) - Chicharro-Luna, Esther; Ortega-Ávila, Ana Belén; Requena-Martínez, Aránzazu; Gijón-Noguerón, Gabriel (Elsevier, 2021)
Diabetic peripheral neuropathy (DPN) is one of the most common complications in diabetes mellitus. It is the disorder that most commonly affects the feet of people with diabetes. The aim of the present study is to determine the relationship between DPN and the presence of deformities in the foot. Material and methods: A descriptive observational study was conducted of 111 patients diagnosed with Diabetes Mellitus (DM) type 1 or 2. All participants were aged at least 18 years and were previously informed in detail about the aims and procedures of the study. Results: Regarding the presence of DPN, the only significant relationships were found for the right foot with the deformity of the second toe (claw, hammer or mallet) (p = 0.017, OR 0.29 [0.10-0.83]) and for the left foot with the deformity of the second toe (p = 0.048; OR: 0.37 [0.14-1.01]), third toe (p = 0.012; OR: 0.29 [0.11-0.79]) and the presence of hallux extensus (p = 0.05; OR: 8.27 [1.05-64.98]). Conclusions: A significant number of foot deformities were observed among these patients with DM, regardless of the presence of DPN. These deformities should be carefully evaluated in order to determine the most appropriate treatment at an early stage, which will reduce the risk of ulceration. Although it should be use with caution to be transferrable to the general population with peripheral neuropathy.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/14144
Keywords: Neuropatía diabética; Diabetes - Complicaciones; Deformities; Diabetic peripheral neuropathy; Foot; Hyperkeratosis